CURRENT ASPECTS OF CORPORATE GOVERNANCE IN NATIONAL DEVELOPMENT BANKS - Бортніков, Геннадій (Socio-economic relations in the digital society, 2019)
National development banks are capable to operate effectively, fulfilling their strategic mission. The task of research is to compare compliance of sound standards of corporate governance by national development banks and Ukrainian state-owned banks in terms of forming the board and disclosing information on the scheme of remuneration of senior executives. All four commercial banks in Ukraine are universal and for various reasons cannot award the status of a full-fledged development bank. However, the author accounts, that creation of a national development bank is possible on the basis of one or more existing banks by their transforming, to save time and resources. If adopt the political decision, the question of a proper corporate governance will be raised, in order to prevent failures. One of the prerequisites for successful attraction of resources in the market and placement of funds in working assets is the  organization and management in compliance with proper standards of corporate governance. The state is able to prove itself as an effective owner (possessor), by preventing the  politicization of the development bank’s business in the interests of certain oligarchic circles or for the sake of short-term benefits. A high management culture will be ensured by setting up prudential and proper selection, evaluation and remuneration of senior executives of state-owned banks, which is a crucial task for the supervisory board. One of the key criteria for selection for right candidates for the positions of bank executives should be their perfect reputation. The costs of retaining senior executives (board members) in terms of remuneration should be reasonable, taking into account not only the market level of salary (which is questionable due to poor transparency), but also to correspond with scale and performance of specific bank. The author processed the management reporting data on remuneration published by national development banks in Europe. Due to the lack of information transparency of state-owned banks in Ukraine in performance evaluation, it is practically impossible to assess whether the policies adopted are adequate and adhered to, and officials properly perform their functions. Thus, the form in scientific research dominates over the content. Status of the state bank requires a higher level of public disclosure of remuneration framework, followed by justification of salary level of senior executives.
Keywords: banks; public sector; development bank; corporate governance; remuneration; management